Improving Students’ Self-Esteem in Learning Mathematics through a Realistic Mathematic Education - Siregar, Rama Nida; Suryadi, Didi; Prabawanto, Sufyani; Mujib, Abdul (FKIP Universitas Lampung, 2022)
This research is motivated by the problem, the low level of self-esteem of students. The purpose of this study was to determine the increase in self-esteem of students with realistic mathematics education in mathematics learning, and to determine student responses to mathematics learning with realistic mathematics learning. This type of research is descriptive research through questionnaire analysis. The instrument used is a self-esteem questionnaire to see self-esteem abilities that have been tested and a questionnaire to see student responses. In this study, data were obtained to see the increase in self-esteem of students with realistic mathematics education in learning mathematics and to see student responses to learning mathematics using mathematics education which were analyzed using a Likert attitude scale. The scale in this self-esteem contains four components, namely: students' assessments of (1) their ability (capability) in mathematics, (2) their success (successfulness) in mathematics, (3) their significance in mathematics, and (4) goodness (worthiness) himself in mathematics The conclusion obtained in this study related to self-esteem in mathematics is that it can be seen as a whole using a realistic mathematical education. It shows that there are 86.56% of students giving positive responses. Keywords: self-esteem, junior high school students, realistic mathematic education. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp1262-1277